Differential effects of parent and peer presence on neural correlates of risk taking in adolescence. Issue 9 (3rd September 2018) - van Hoorn, Jorien; McCormick, Ethan M; Rogers, Christina R; Ivory,, Susannah L; Telzer, Eva H
Abstract: Adolescence is a developmental period associated with increased health-risk behaviors and unique sensitivity to the input from the social context, paralleled by major changes in the developing brain. Peer presence increases adolescent risk taking, associated with greater reward-related activity, while parental presence decreases risk taking, associated with decreased reward-related activity and increased cognitive control. Yet the effects specific to peers and parents are still unknown. The current functional magnetic resonance imaging (fMRI) study compared within-person peer and parent influences on risky decision-making during adolescence (ages 12–15 years; N  = 56). Participants completed the Yellow Light Game (YLG), a computerized driving task, during which they could make safe or risky decisions, in the presence of a peer and their parent. Behavioral findings revealed no effects of social context on risk taking. At the neural level, a collection of affective, social and cognitive regions [ventral striatum (VS), temporo-parietal junction (TPJ), and dorsolateral prefrontal cortex (dlPFC)] was more active during decision-making with peers than parents. Additionally, functional connectivity analyses showed greater coupling between affective, social and cognitive control regions (VS-insula, VS-TPJ) during decision-making with parents than peers. These findings highlight the complex nature of social influence processes in peer and parent contexts, and contribute to our understanding of the opportunities and vulnerabilities associated with adolescent social sensitivity.